2000
DOI: 10.1088/0031-9155/45/7/308
|View full text |Cite
|
Sign up to set email alerts
|

Artefacts in multi-echoT2imaging for high-precision gel dosimetry: II. Analysis ofB1-field inhomogeneity

Abstract: In BANG gel dosimetry, the spin-spin relaxation rate, R2 = 1/T2, is related to radiation dose that has been delivered to a gel phantom. R2 is calculated by fitting the pixel intensities of a set of differently T2-weighted base images. The accuracy that is aimed for in this quantitative MR application is about 5% relative to the maximum dose. In a conventional imaging MR scanner, however, several imaging artefacts may perturb the final dose map. These deviations manifest themselves as either a deformation of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(43 citation statements)
references
References 43 publications
1
41
0
1
Order By: Relevance
“…Whereas T 2 -weighted images are used in the clinic, a collection of these images are used to calculate R 2 maps. Although theoretically, the use of T 1− or T 2− weighted images is not excluded, it is found that main magnetic field ( B 0 ) (De Deene et al 2001a) radio-frequency field ( B 1 ) (De Deene et al 2000b) inhomogeneities have a detrimental impact on the accuracy of the dose reading. These effects are largely compensated by the use of quantitative R 2 maps as these effects are in first order proportional to the signal intensity.…”
Section: Evaluation Of Polymer Gel Dosimetersmentioning
confidence: 99%
“…Whereas T 2 -weighted images are used in the clinic, a collection of these images are used to calculate R 2 maps. Although theoretically, the use of T 1− or T 2− weighted images is not excluded, it is found that main magnetic field ( B 0 ) (De Deene et al 2001a) radio-frequency field ( B 1 ) (De Deene et al 2000b) inhomogeneities have a detrimental impact on the accuracy of the dose reading. These effects are largely compensated by the use of quantitative R 2 maps as these effects are in first order proportional to the signal intensity.…”
Section: Evaluation Of Polymer Gel Dosimetersmentioning
confidence: 99%
“…64,207,[228][229][230] In particular, attention is required to minimize uncertainties that originate from the technical challenges of controlling magnetic field uniformity and gradients with sufficient precision, avoiding MRI sequences that cause excessive temperature increase associated with RF energy deposited in the gel during MR imaging. 228 For MR measurements requiring high accuracy and highspatial resolution, long imaging times ͑several hours͒ may be required to achieve the low uncertainty and high spatial resolution associated with standard dosimeters.…”
Section: Vb3 Readout Techniquesmentioning
confidence: 99%
“…The main advantage of this evaluation technique is that limited access to MRI facilities is not an issue or is the need to build or purchase specialized optical scanning equipment. It should be noted that where, for instance, MRI has evaluation problems such as in homogeneities or temperature dependence (De Deene et al, 2000a, 2000bDe Deene & Wagter, 2001), x-ray CT evaluation has its own limitations. However, as is the case with MRI evaluation of polymer gel dosimeters , it has been shown that x-ray CT evaluation techniques require the CT scanner be commissioned specifically for gel dosimetry before use (Hill et al, 2005).…”
Section: X-ray Ct Scanningmentioning
confidence: 99%